Effect of COVID-19 lockdown on sleep behavior and screen exposure time: an observational study among Indian school children. Issue 4 (3rd April 2022) - Dutta, Koumi; Mukherjee, Ruchira; Sen, Devashish; Sahu, Subhashis
ABSTRACT: Lockdown is an important measure that has been globally adopted to reduce the spread of the contagious disease caused by SARS CoV-2. The imposed schedule and confinement led to extensive use of digital media and rise in sedentary activity drastically. The escalated duration of screen exposure causes disruption in sleep behavior. An online survey was conducted to comprehend the effect of lockdown on sleep behavior and screen exposure time on school children. Screen exposure time involved with various electronic gadgets was also analyzed. It was observed that the social jet lag and sleep debt were significantly less during lockdown than before it. Inertia during lockdown significantly increased. The difference between screen exposure time on weekdays before lockdown and weekends during lockdown was identified to be the highest. Three clusters based on sleep behavior and duration of screen time were identified of which Cluster 2 revealed simultaneous existence of high sleep duration and screen time. These baseline data on sleep parameters and duration of exposure to the screen will help us in devising approaches to mitigate the evident disruption this unprecedented phase has brought about.